The archaeology of Greek and Roman Troy - Rose, Charles Brian. (Cambridge ; New York)
xv, [24], 406 sayfa
Keywords: “The Archaeology of Greek and Roman Troy provides a synthetic overview of all excavations that have been conducted at Troy, from the nineteenth century through the latest discoveries between 1988 and the present. Charles Brian Rose traces the social and economic development of the city and related sites in the Troad, as well as the development of its civic and religious centers from the Bronze Age through the early Christian period, with a focus on the settlements of Greek and Roman date. Along the way, he reconsiders the circumstances of the Trojan War and chronicles Troy's gradual development into a Homeric tourist destination and the adoption of Trojan ancestry by most nation-states in medieval Europe.” --